The Effect Of Learning Methods On Motivation And Results Of Learning Skill Lab Physical Examination Of Baby Students Midwifery Stikes Husada Jombang - Sumini, Gempi Tri; Indasah, Indasah; Nurwijayanti, Nurwijayanti (Universitas STRADA Indonesia, 2019)
Learning method is a presentation technique that is mastered by a teacher to present subject matter to students in the class either individually or in groups so that the subject matter can be absorbed, understood and utilized by students. The purpose of this study is to determine the effect of learning methods on motivation and learning outcomes of the skills of the midwifery student's physical examination lab. The research design used was True Experimental Design (randomized Pretest-Posttest Control Group Design.) Independent variable learning method, dependent variable motivation, learning outcomes. Dependent variable data collection using quisioner and observation. The study population was all V semester midwifery students at Stikes Husada Jombang. Simple random sampling sampling technique with a sample of 60 students. Data were analyzed using the Wilcoxon signed rank test. Based on the results of the Wilcoxon statistical test between learning motivation before and after the simulation p = 0.003 where p <Î± (0.05), the results of the Wilcoxon statistical test between learning outcomes before and after the method obtained p = 0,000 where p <Î± (0.05) , While the homogeneity test using the lavene test obtained a value of p = 0,000 <value Î± = 0.05, meaning that the data in the sample data group were homogeneous or had the same variant.Efforts to overcome the problematic problem in the implementation of the physical examination of the baby midwifery students of Stikes Husada Jombang who have capable quality can be overcome by demonstration learning methods, simulations and role play that lead to increased learning outcomes, ie all students in the group giving learning methods are proficient in physical examination the baby and student motivation also affect the learning outcomes of the baby's physical examination lab skills.